2020
DOI: 10.3390/app10186226
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion Performance of the Full-Active Flapping Foil in Time-Varying Freestream

Abstract: A numerical investigation of the propulsion performance and hydrodynamic characters of the full-active flapping foil under time-varying freestream is conducted. The finite volume method is used to calculate the unsteady Reynolds averaged Navier–Stokes by commercial Computational Fluid Dynamics (CFD) software Fluent. A mesh of two-dimensional (2D) NACA0012 foil with the Reynolds number Re = 42,000 is used in all simulations. We first investigate the propulsion performance of the flapping foil in the parameter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They found that the flapping wing sweep angle is not the key factor for the thrust generated by the flapping wing. Qi et al [ 30 ] from China National Oceanographic Research Center studied the propulsion performance and hydrodynamic characteristics of the flapping wing under time‐varying free flow and used the finite volume method to calculate the unsteady Reynolds average Navier–Stokes equation. They found that the time‐varying flow had little effect on the propulsion performance of flapping wing.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the flapping wing sweep angle is not the key factor for the thrust generated by the flapping wing. Qi et al [ 30 ] from China National Oceanographic Research Center studied the propulsion performance and hydrodynamic characteristics of the flapping wing under time‐varying free flow and used the finite volume method to calculate the unsteady Reynolds average Navier–Stokes equation. They found that the time‐varying flow had little effect on the propulsion performance of flapping wing.…”
Section: Introductionmentioning
confidence: 99%